Pigments based on silica-coated gold nanorods: synthesis, colouring strength, functionalisation, extrusion, thermal stability and colour evolution - Gautier, Cyrille; Cunningham, Alastair; Si-Ahmed, Lynda; Robert, Gilles; Bürgi, Thomas (Gold bulletin, 2010)
The intense plasmon absorption bands of gold nanorods (GNRs) with peak extinction coefficients up to 6.4×109 M−1 cm−1 as well as their expected high stability make GNRs promising candidates for the colouration of bulk materials. The comparison of the integrated absorption in the visible region of GNRs with those of commercial organic pigments shows that the colouring strength of GNRs is 4 to 8 times higher.
Gesehen am 20.02.2023